Optimization of the Extraction of Rosmarinic Acid and Carnosic Acid from Rosmarinus officinalis L. with Deep Eutectic Solvents by Response Surface Methodology - Lingna LI; Jiwei YANG; Lifen ZHANG; Mengjian ZHAO; Zhenhua WANG; Chengjun MA (Shipin gongye ke-ji, 2023)
Objective: To extract rosmarinic acid (RA) and carnosic acid (CA) from Rosmarinus officinalis L. using deep eutectic solvents (DESs) simultaneously and optimize the extraction process, which provided the basis for development and utilization of its antioxidant components. Methods: firstly, the DESs with the highest yield of RA and CA was screened out from 37 different DESs combination. Then, the effects of different molar ratio, water content (%), liquid-solid ratio (mL/g), extraction time (min) and extraction temperature (℃) on the yield of RA and CA were studied by single factor experiments. On this basis, the response surface method was employed to optimize the extraction process. Finally, the extraction yields of RA and CA and the DPPH· free radical scavenging ability were compared between DESs and traditional solvent extraction (80% ethanol, n-hexane). Results: lactic acid/1,4-butanediol (molar ratio 1:2) DESs was chosen as the optimal extraction solvent, and the optimum extraction parameters were as follow: Water content (12%), liquid-solid ratio (44:1 mL/g), extraction time (60 min), and extraction temperature (40℃). Under these conditions, the yields of RA and CA were 20.247 and 34.086 mg/g, respectively. Compared with the traditional extraction process, the total yields of RA and CA were increased by 1.4 times (ethanol) and 1.5 times (n-hexane), respectively, and the extraction time was shorted. Using vitamin C (0.03 mg/mL, scavenging rate 89.77%) as control, under the same concentration of R. officinalis L. (0.625 mg/mL), DESs scavenging rate was 73.17%, which was higher than ethanol (66.93%) and n-hexane (62.57%). Conclusions: DESs extraction method could simultaneously extract hydrophilic RA and hydrophobic CA from R. officinalis L., with higher yield and antioxidant activity. It could be a green, environmentally friendly and efficient extraction method for antioxidants from R. officinalis L..